Photobiomodulation effects of 808 nm and 915 nm diode lasers on proliferation and osteogenic differentiation of Buccal fat pad stem cells - Ardavan Etemadi; Raika Norouzinia; Mahshid Hodjat; Neda Hakimiha (Photodiagnosis and Photodynamic Therapy)
Aim: Photobiomodulation therapy (PBM) is a promising adjunct in tissue engineering due to its ability to stimulate cell proliferation and differentiation. This study evaluated the effects of PBM on buccal fat pad-derived stem cells (BFPSCs) using two diode laser wavelengths. Methods: BFPSCs were divided into seven groups: six received laser irradiation and one served as control. Three groups were treated with a 915 nm laser and three with an 808 nm diode laser, each at energy densities of 2, 4, and 6 J/cm². Cell proliferation was assessed using the MTT assay, while osteogenic differentiation was evaluated by Alizarin red staining after 14 days. Alkaline phosphatase activity was measured after 7 days. Expression levels of osteocalcin (OCN), Osteopontin (OPN), and Runt-related transcription factor 2 (RUNX2) were measured by RT-PCR on days 7 and 14. Results: PBM significantly enhanced cell proliferation, particularly at 4 J/cm² (808 nm) and at 4 and 6 J/cm² (915 nm). Upregulation of OCN and OPN were detected in most irradiated groups. RUNX2 expression was higher in all PBM groups. Alizarin Red staining and alkaline phosphatase activity results confirmed PBM’s stimulatory effects. Conclusion: PBM, especially at 915 nm, enhances the proliferation and osteogenic differentiation of BFPSCs, suggesting potential benefits for bone reconstruction.